Anxiety Disorders and Their Effects on Student Learning Outcomes in State Vocational Schools in Makassar City - Nuraisyiah, Nuraisyiah (Cita konsultindo, 2023)
This study aims to determine the effect of anxiety disorders on student learning outcomes at SMK Negeri in Makassar City. The variables in this study were anxiety disorders (X) and learning outcomes (Y) as measured by the Likert scale. The population was all students of class XI at SMK Negeri in Makassar City, totaling 365 students and the sample was drawn using the Proportionate Stratified Random Sampling method which obtained a sample size of 182 students. Data collection techniques used are questionnaires and documentation. The data analysis technique is analysis of data validity and statistical analysis. The results showed that anxiety disorders affect student learning outcomes in accounting class XI at SMK Negeri in Makassar City through nine indicators, namely: tension, confusion, worry, difficulty concentrating, unable to sleep, palpitations, excessive cold sweats, frequent tremors, and stomach ulcers have a negative and significant effect. This means that if students experience anxiety disorders it will reduce student learning outcomes.